How Learning Motivation and Organizational Activities Influence Career Growth Among UINSU Scholarship Alumni? - Siregar, Padrie Payung; Juliana Nasution; Atika (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2025)
This study aims to analyze the effect of learning motivation and organizational activeness on the career development of scholarship alumni at the State Islamic University of North Sumatra (UINSU). The method used is quantitative research with a survey approach, involving 30 alumni respondents who have received scholarships and are active in campus organizations. The results showed that learning motivation had no significant effect on career development, while organizational activeness had a significant positive effect. Simultaneously, these two variables contribute to career development with a contribution of 26.7%. The findings confirm the importance of involvement in organizations to develop non-academic skills required in the world of work, as well as showing that learning motivation, although important, is not enough to guarantee career success without the support of practical experience. This research provides insights for universities in designing more effective coaching programs for scholarship students, so that they are better prepared to face challenges in a competitive job market.